The Inclusion of Social Character Values in Buku Bahasa Inggris for 10th Graders (Universitas Negeri Semarang, 2021)
Textbooks play an important role in teaching and learning activities. The revisions to the curriculum still kept character education at their center, even strengthening its implementation. Indonesia's current president, Mr. Jokowi, has a plan called